KONSEP DAN KARAKTERISTIK WALIYULLAH DALAM SURAT YUNUS AYAT 62 - Muammad Fery; Mamluatun Ni'mah; Mujiburrahman mujiburrahman (Education for Islamic Studies Department, Islamic University of Majapahit (Universitas Islam Majapahit) Mojokerto, Indonesia, 2023)
This study aims to study and analyze Waliyullah in the holy book of the Qur'an, Surat Yunus verse 62. This research started with a wrong understanding of the community about the concept of Waliyullah, the community assumed that what they got, but all the allegations that he received as a basis were very distorted by explanation of the Qur'an so that researchers are interested in analyzing the concept and characteristics of Waliyullah in Surat Yunus verse 62 and how to get guardianship in the perspective of the Qur'an. The path and the outline rules in this study have the aim of finding a truth about the concepts and characteristics of Waliyullah which are contained in Surat Yunus verse 62. This study is of the type of literature (library research) and this study uses a descriptive and thematic analysis method to analyze. Then the inductive method is used by the researcher in drawing a conclusion that has been generated from the analysis. The results of this study are: first, Waliyullah, are people who do not have anxiety or sadness within themselves. secondly, Waliyullah who always has faith and belief in the One and Only God and his Prophet, he always does what Allah commands and stays away from what is forbidden, gets good news in this world and the hereafter. Third, those who leave the worldly affairs of warok, towards something that has no benefit for them, are kind and not angry towards those who believe, then are harsh towards the Quraysh infidels.